Gender gap in IT in Latin America - Guzman, Indira R. Indira R. (2020)
The underrepresentation of women in IT related majors such as computer science, computer engineering, and information systems (IS) has been evident all over the world. As a result, many private and public institutions have created programs aimed to increase enrollment, recruitment, and placement of women in the field and reduce the gender gap in the field. Several journal publications about this kind of research can be found in the scientific literature about studies mostly conducted in the United States, Europe, Asia and Australia, but very few publications about this kind of research in Latin American countries is available in the literature despite the fact that in the last ten years, countries in Latin America also developed a variety of programs with the same goal with the support of international organizations like the United Nations Educational, Scientific and Cultural Organization (UNESCO), giant technology corporations like IBM, and local governments. There are very few publications in international scientific outlets about Gender Gap in IT in Latin America. In this panel, seven Latin American academics will share recent related projects they have been part of, compare project results, challenges, and discuss what kind of dissemination practices could be more appropriate.